Application of seismic attribute analysis techniques to multi-scale natural fractures description: a case study of the Longmaxi-Wufeng formation in H shale gas block, Yangtze plate, China - Xie, Qinghui; Chen, Junhao; Zhao, Chunduan; Li, Qingshan; Guan, Shoujun; Wang, Junqin (Frontiers in Earth Science, 2024)
The H shale gas block in the Yangtze plate of China has undergone multistage tectonic evolution, which has resulted in the development of faults and natural fractures that are multistage, multi-scale, multi-type, and multi-strike in nature. . To precisely characterize the natural fractures, this study used the seismic attribute analysis method to conduct a multi-scale prediction and natural fracture modelling. Initially, manual fault interpretation and the conventional seismic attributes including variance attribute, curvature and edge detection are used to interpret large-to medium-scale faults.Subsequently, the ant-tracking attribute based on the divided-frequency seismic cubes is used to predict and quantitatively interpret the mid-and small-scale fractures; The third step is to quantitatively divide the ant-tracking attribute value into multiple scales and convert them linearly into fracture intensity. The fourth step is to establish a multi-scale fracture model. This approach has established a comprehensive prediction workflow, progressing from large-scale to small-scale analysis, and shifting from qualitative to quantitative assessment. Compared with traditional fracture prediction and modeling methods, this method not only enhances the accuracy, but also satisfies the engineering requirements of multi-scale modeling.By applying the method in the H shale gas block, we gained a microscopic understanding of the fractures, which are predominantly NW, NE, and nearly NS trending, with a minimal occurrence of nearly EW trending faults/fractures. This method can be effectively applied to characterize multi-scale fractures in areas similar to the geological background of the H shale gas block.